2019
DOI: 10.1093/conphys/coz063
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on performance and physiology of two prairie stream minnows

Abstract: The observed distributions of two grazing minnows differ along a stream-size gradient in grassland streams and may be linked to temperature. In laboratory experiments, we assayed a suite of physiological traits along a temperature gradient and found that species differed in critical thermal maxima, with subtle differences in other traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…We found T up for Bluegill ETS enzyme activity (acclimated to 21°C) to be 33.7°C, while CT max for Bluegill acclimated at ~20–26°C ranged from 31.5°C to 37.5°C (Beitinger et al, 2000). Central Stoneroller Campostoma anomalum acclimated to 23°C displayed loss of equilibrium at 35.8°C with reported CT max as high as 38°C (Chagnon & Hlohowskyj, 1989; Frenette et al, 2019; Mundahl, 1990), whereas we found Largescale Stoneroller ETS enzyme T up to be 40.2°C. Red Shiner Cyprinella lutrensis is a widely‐distributed member of the Cyprinella genus; individuals acclimated to 20°C and 22°C experienced loss of equilibrium at 34°C and 36.2°C, respectively (Carrier & Beitinger, 1988); we found T up for ETS enzyme activity to be 36.6°C for a member of the same genus, Tallapoosa Shiner.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…We found T up for Bluegill ETS enzyme activity (acclimated to 21°C) to be 33.7°C, while CT max for Bluegill acclimated at ~20–26°C ranged from 31.5°C to 37.5°C (Beitinger et al, 2000). Central Stoneroller Campostoma anomalum acclimated to 23°C displayed loss of equilibrium at 35.8°C with reported CT max as high as 38°C (Chagnon & Hlohowskyj, 1989; Frenette et al, 2019; Mundahl, 1990), whereas we found Largescale Stoneroller ETS enzyme T up to be 40.2°C. Red Shiner Cyprinella lutrensis is a widely‐distributed member of the Cyprinella genus; individuals acclimated to 20°C and 22°C experienced loss of equilibrium at 34°C and 36.2°C, respectively (Carrier & Beitinger, 1988); we found T up for ETS enzyme activity to be 36.6°C for a member of the same genus, Tallapoosa Shiner.…”
Section: Discussionsupporting
confidence: 38%
“…Campostoma anomalum acclimated to 23°C displayed loss of equilibrium at 35.8°C with reported CT max as high as 38°C (Chagnon & Hlohowskyj, 1989;Frenette et al, 2019;Mundahl, 1990) (Westhoff et al, 2021), and although these comparisons are promising, additional work combining CT max and ETS activity, especially with common acclimation conditions, is needed to better define the relationship between them.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature is also a strong driver of largemouth bass distributions (Bae et al, 2018; Sowa & Rabeni, 1995), but was not considered in this analysis. Temperature may have explained the negative co‐occurrence and abundance patterns between southern redbelly dace and largemouth bass, as dace are known to inhabit relatively small, cool streams (Frenette et al, 2019). Sampling variability, such as local conditions at sites probably also introduced variation in our ability to detect largemouth bass presence.…”
Section: Discussionmentioning
confidence: 99%
“…Wildfire‐mediated fluxes vary with topology. Historically, wildfires in the western United States tended to occur in forested headwater catchments, for example, in the Yellowstone fires (Minshall, 2003 ) and wildfires in New Mexico, United States (Frenette et al., 2019 ). Disturbances tend to have a larger impact in headwaters, and these impacts are attenuated downstream (Benda et al., 2004 ).…”
Section: Wildfire Effects On Aquatic Habitatmentioning
confidence: 99%